Managers in the Global Economy: A Multilevel Analysis. Issue 2 (1st May 2016) - Kaya, Yunus; Martin, Nathan D.
Abstract : We examine individual- and country-level determinants of managerial employment, using data from the 1989 to 2009 waves of the World Values and European Values Surveys (n = 89, 336 employed adults in 59 countries). Reflecting the rise of the transnational capitalist class, we find that factors related to globalization and international political institutions are most strongly associated with opportunities to join the managerial class relative to factors related to the business-cycle or development. Additionally, in a subset of countries with detailed occupational information, we find that global trade has a particularly strong, positive association with the odds of being a corporate manager in a large firm.